Registration of twelve sorghum germplasm lines tolerant to greenbug feeding damage - Kofoid, Kenneth D.; Perumal, Ramasamy; Reese, John C.; Campbell, L. R. (My University, 2012)
The biotypic diversity of the greenbug [Schizaphis graminum (Rondani)] and development of lines with tolerance to greenbug feeding are ongoing concerns of sorghum [Sorghum bicolor (L.) Moench.] breeding programs in the United States. The genetic male sterile population KP7B and four germplasm sources (IS 25246, IS 27002, IS 27834, and IS 27903) were used in population improvement for tolerance to greenbug feeding. Differences in tolerance were quantified by estimating the chlorophyll content of leaf tissues using a SPAD chlorophyll meter following a 7-d period of greenbug feeding on leaves. Twelve sorghum germplasm lines KS 121 (Reg. No. GP-718, PI 651584), KS 122 (Reg. No. GP-719, PI 651585), KS 123 (Reg. No. GP-720, PI 651586); KS 124 (Reg. No. GP-721, PI 651587), KS 125 (Reg. No. GP-722, PI 651588), KS 126 (Reg. No. GP-723, PI 651589), KS 127 (Reg. No. GP-724, PI 651590), KS 128 (Reg. No. GP-725, PI 651591), KS 129 (Reg. No. GP-726, PI 651592), KS 130 (Reg. No. GP-727, PI 651593), KS 131 (Reg. No. GP-728, PI 651594), and KS 132 (Reg. No. GP-729, PI 651595) with enhanced tolerance to greenbug feeding were developed and released by the Kansas Agricultural Experiment Station in October 2007. These lines are three-dwarf (dw[subscript 1], Dw[subscript 2], dw[subscript 3], dw[subscript 4]) in height, photoperiod-insensitive, and possess unique combinations of plant color and tolerance to damage by greenbug biotypes E, I, and K. All 12 lines restore fertility in the A1 cytoplasm system and hence can be used as R-lines in breeding programs to develop new hybrids with greenbug feeding tolerance.
Citation: Kofoid, K. D., Perumal, R., Reese, J. C., & Campbell, L. R. (2012). Registration of twelve sorghum germplasm lines tolerant to greenbug feeding damage. Retrieved from http://krex.ksu.edu
Keywords: Sorghum; Greenbug; Schizaphis graminum (Rondani); Tolerance to damage